Writing Assignment: Exercise on Sociology and History - Foran, John (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Please prepare a three-page typed, double-spaced essay on one of the two questions below. Carefully consider all the parts of the questions before you write. Edit your writing for typos and for style. Cite the relevant readings in your answer. Option One: Collective Social History: The Work of E. P. Thompson; Option Two: Connecting a Life to a Society – the Work of Carlo Ginzburg